Pengembangan aplikasi “SIMBA” (Social studies instructional media based android) untuk mata pelajaran IPS kelas VII SMP - Neni Wahyuningtyas; M. Haris Yahya (JINoP (Jurnal Inovasi Pembelajaran), 2021)
Media is an important component in multidisciplinary social studies learning that must be presented in an integrated method. This study aimed to design learning media "SIMBA" (Social Studies Instructional Media Based on Android) and to analyze the feasibility based on an assessment by experts and students. The stages in this research and development were carried out by adopting 4D development, namely: define, design, develop, and disseminate. Due to limitations, the research was only carried out at the development stage, The research data is a feasibility assessment using a Likert scale from expert and VII grade students at SMP Negeri 21 Malang were collected using a questionnaire. The data were then analyzed by using the percentage descriptive technique. The results of the development were learning media which contains six menu components, namely: the competency and objectives, learning materials, our surroundings, videos, quizzes, and the developer menu. The results of the assessment from experts are “Very Appropriate”. While the students showed similar things which means the learning media "SIMBA" was feasible and could meet the needs of students in the learning process. Based on the weaknesses of this study, it is necessary to develop similar applications in other subjects that are capable of producing offline applications and can be accessed by teachers and students in the future.